2017
DOI: 10.1097/ccm.0000000000002366
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm Activation in Ventilated Patients Using a Novel Transvenous Phrenic Nerve Pacing Catheter

Abstract: In this First-in-Human series, diaphragm pacing with a temporary catheter was safe and effectively contributed to ventilation in conjunction with a mechanical ventilator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 8 publications
1
35
0
1
Order By: Relevance
“…Preclinical work showed that this technique could reduce the development of diaphragm type II fiber atrophy [ 84 , 85 ]. Recently, Reynolds et al presented a first-in-human series of temporary transvenous phrenic nerve pacing in surgical patients and showed that this technology delivered safe and effective diaphragm contractions [ 86 ]. This strategy is currently being studied as potential intervention for improving diaphragm strength in difficult-to-wean patients (NCT03096639).…”
Section: Future Approaches To Lung and Respiratory Muscle-protective mentioning
confidence: 99%
“…Preclinical work showed that this technique could reduce the development of diaphragm type II fiber atrophy [ 84 , 85 ]. Recently, Reynolds et al presented a first-in-human series of temporary transvenous phrenic nerve pacing in surgical patients and showed that this technology delivered safe and effective diaphragm contractions [ 86 ]. This strategy is currently being studied as potential intervention for improving diaphragm strength in difficult-to-wean patients (NCT03096639).…”
Section: Future Approaches To Lung and Respiratory Muscle-protective mentioning
confidence: 99%
“…Sepsis is among the study’s exclusion criteria, and as such a worsening diaphragmatic dysfunction through sepsis-related mechanisms appears relatively unlikely. Of note, short-term human uses of the LIVE® Catheter have not unveiled significant safety concerns [30]. Finally on this point, it should be kept in mind that the potential benefits of TTVDP in patients who are difficult to wean from MV are major.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to human testing, bench and animal testing ensured that the device met the minimum design requirements for various measures, including (but not limited to) system integrity, biocompatibility, sterility, and packaging/storage integrity. The safety of the system was initially tested in a first-in-human study [30], and this RESCUE 2 study will optimize the risk/benefit balance by (1) excluding patients with conditions thought to increase procedural risks or to decrease the probability of efficacy; (2) selecting experienced investigators and experienced clinical research teams; (3) training investigators on the protocol implementation methods; and (4) utilizing experienced medical professionals to continuously monitor study patients during the catheter placement procedures and during therapy sessions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In einer klinischen Untersuchung bei 22 Patienten, die sich elektiven chirurgischen Eingriffen unterzogen (Korrektur Vorhofseptumdefekt), konnten sowohl die grundsätzliche Anwendbarkeit der Methode als auch die effektive Auslösung von Zwerchfellkontraktionen aufgezeigt werden und damit die grundsätzliche Machbarkeit im klinischen Setting [584].…”
Section: Atemmuskelunterstützung Durch Indirekte Und Direkte Stimulatunclassified